PEMANFAATAN LIMBAH SABUT KELAPA ( Cocos nucifera L) DAN SERAT TANDAN KOSONG KELAPA SAWIT (Elais guineensis JACQ) SEBAGAI KOMBINASI BAHAN BAKU PEMBUATAN PAPAN PARTIKEL - Adam Maulana; Udiantoro Udiantoro; Lya Agustina (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2019)
The utilization of coconut fiber that has not been optimal is one of the opportunities so that the waste has added value, one of which is to process it into particle board. Objective research is to best composition particle board making from coconut coir waste material and TKKS to produce qualified particle board. The method used was a complete randomized design (RAL) with 3 treatment, single factor treatment ie the composition of raw materials in the form of coconut husk and TKKS. Comparison of the particle-making composition of particle board P0: 100% coco fiber: 0% of oil palm empty bunch fibers, P1: 75% : 25%, P2: 50% : 50%, P3: 25% : 75%, P4: 0% : 100%. Best results the combination of raw material composition of particle board is in the treatment of P0 (100% coco fiber: 0% of oil palm empty bunch fiber) with a density value of 0.43 g / cm³, moisture content 7.0%, Modulus of Elasticity - MoE 2.037.45 kg / cm2 and the Modulus of Rupture - MoR 46.14 kg / cm².